Quick Response (QR) Code as Part of Digital Muslim Media in Islamic Da'wa at The Qatar World Cup - Peristiwo, Hadi; Anugrah, Ahlam Tri (Digital Muslim Review, 2023)
A unique phenomenon occurred during the World Cup event in Qatar in 2022. Within a week of the Qatar World Cup, there were already 558 people who converted to Islam. Many soccer fans who specifically watched the World Cup were interested in deepening Islam and then converting to the religion. From the perspective of da’wa communication, the da’wa media through digital media carried out by Qatar using the Quick Response (QR) Code was a real effort to show the tolerant face of Islam to the world. The main purpose of this research is to explain the role of the Quick Response (QR) Code as a part of digital da’wa media in organising the World Cup in Qatar. This research is a type of qualitative research with a descriptive analysis. The article shows that the da’wa carried out by Qatar during the World Cup using digital media QR Code was part of the da’wa strategy by inviting people outside of Islam bil hikmat wal mauidhah al-hasanah and this method was very appropriate to describe a friendly and peaceful Islamic religion to the world. In general, the theoretical significance of this research is to contribute to the development of Islamic da’wa communication through digital media.